(a+6)(a+4)=

Simple and best practice solution for (a+6)(a+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (a+6)(a+4)= equation:


Simplifying
(a + 6)(a + 4) = 0

Reorder the terms:
(6 + a)(a + 4) = 0

Reorder the terms:
(6 + a)(4 + a) = 0

Multiply (6 + a) * (4 + a)
(6(4 + a) + a(4 + a)) = 0
((4 * 6 + a * 6) + a(4 + a)) = 0
((24 + 6a) + a(4 + a)) = 0
(24 + 6a + (4 * a + a * a)) = 0
(24 + 6a + (4a + a2)) = 0

Combine like terms: 6a + 4a = 10a
(24 + 10a + a2) = 0

Solving
24 + 10a + a2 = 0

Solving for variable 'a'.

Factor a trinomial.
(6 + a)(4 + a) = 0

Subproblem 1

Set the factor '(6 + a)' equal to zero and attempt to solve: Simplifying 6 + a = 0 Solving 6 + a = 0 Move all terms containing a to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + a = 0 + -6 Combine like terms: 6 + -6 = 0 0 + a = 0 + -6 a = 0 + -6 Combine like terms: 0 + -6 = -6 a = -6 Simplifying a = -6

Subproblem 2

Set the factor '(4 + a)' equal to zero and attempt to solve: Simplifying 4 + a = 0 Solving 4 + a = 0 Move all terms containing a to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + a = 0 + -4 Combine like terms: 4 + -4 = 0 0 + a = 0 + -4 a = 0 + -4 Combine like terms: 0 + -4 = -4 a = -4 Simplifying a = -4

Solution

a = {-6, -4}

See similar equations:

| 3/7•3 | | 12+(13+y)=25+7 | | 450000-22000x=12000x+(-155000) | | 3x-7=x+14 | | X^2+8x+8=2x | | 3x-7=x+18 | | 450000-22000x=12000x+(155000) | | ydx+(x^2-4x)dy=0 | | (-3ln+lnx)=0 | | x^3-16x-16=0 | | X^2=-12x+64 | | 7+3(x-7)=1-5(x-6) | | -7k=-6k^2 | | -60=x^2-16x | | 2j^2-4j-30=0 | | (4x+3)+57=180 | | (-2x-50)(x+17)=0 | | 3X+42=84 | | 2x=(x+13)+62 | | -1+-4r=-20 | | 1+(6+14)=(1+x)+14 | | -2y+1=y+5 | | 3(32x-256)=0 | | (x-2)(-2x+1)=0 | | 6b^2+19b+15=0 | | 3.9x-6.47=2.5 | | (2x-1)(x-12)=0 | | 6y-2+8y+14+42=180 | | 3/8-1/4x5/6 | | 7+35x=15x+39 | | x^2+12m+26=0 | | 2(11x-3)=104 |

Equations solver categories